ANALISIS STRATEGI PENGEMBANGAN DAN DAYA SAING UMKM MELALUI STUDI KASUS PERENCANAAN, DUKUNGAN, DAN MOTIVASI USAHA PADA UMKM GUMANTEA - Acep Hidayat; Edo Adji Nugroho; Mochamad Gilang Ramadhan; Muhammad Ilham Sapurta; Ujang Suherman (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study analyzes the decision-making process in UMKM Gumantea, a herbal tea micro-enterprise originating from Yogyakarta and operating in Karawang. The research focuses on four managerial aspects: labor management, capital allocation, raw material decisions, and marketing strategies. A qualitative descriptive method with a single case study approach was applied through in-depth interviews, observations, and documentation. Findings reveal that decision-making is shaped by resource limitations and the central role of the owner. Labor decisions are intuitive and flexible but lack long-term efficiency. Capital decisions prioritize financial safety, resulting in gradual business growth. Raw material decisions are the most strategic, emphasizing quality differentiation through consistent sourcing from Yogyakarta. Marketing decisions rely on simple yet adaptive strategies such as the “Jumat Berkah” promotion and basic social media utilization. These findings align with Simon’s bounded rationality, Scott & Bruce’s decision-making styles, and Robbins’ decision stages. The study concludes that UMKM decisions tend to be practical, situational, and experience-driven, highlighting the need for strengthened managerial systems to enhance long-term effectiveness.